Compute each of these double sums.

SolutionStep 1In this problem, it is given that we have to find the sum of the value.a)(i + j)(i + j) = ( (i + 1) +(i + 2) + (i + 3) ) = ( 3i + 6) ` = 3( ( i + 2) ) = Here, = 1 + 2 = 3 and = 2 + 2 = 4Substitute the value back in a previous equation (i + j) = = 3( 3 + 4 ) = 3 * 7 = 21Hence, (i + j) = 21Step 2b)(2i +3 j)(2i +3j) = ((2i + 3*0) +(2i + 3*1) +(2i + 3*2) + (2i + 3*3) ) = (8i + 18) = 8 ( ) + 18 )Here, = 0 + 1 + 2 = 3 and 18 = 18 + 18 + 18 = 54Substitute...